A miniaturized hairpin resonator for the high selectivity of WLAN bandwidth - S. M. Kayser Azam; Muhammad I. Ibrahimy; S. M. A. Motakabber; A. K. M. Zakir Hossain; Md. Shazzadul Islam (Institute of Advanced Engineering and Science, 2019)
In this article, a miniaturized hairpin resonator has been presented to introduce the high selectivity of Wireless Local Area Network (WLAN) bandwidth. In the construction of the hairpin resonator, short-circuited comb-lines are electrically coupled with the two longer edges of a rectangular-shaped loop. The hairpin resonator has been designed and fabricated with the Taconic TLX-8 substrate with a center-frequency at 2.45 GHz. The resonator exhibits a second order quasi-Chebyshev bandpass response. A low insertion loss has been found as -0.36 dB with a minimum return loss as -36.71 dB. The filtering dimension of this hairpin resonator occupies a small area of 166.82 mm2. This hairpin resonator is highly selective for the bandpass applications of the entire WLAN bandwidth.